Improving Estimation of Labor Market Disequilibrium Using Shortage Indicators, with an Application to the Market for Anesthesiologists - Matthew Baird; Lindsay Daugherty; Krishna B. Kumar (Institute of Labor Economics (IZA), 2019)
While economic studies often assume that labor markets are in equilibrium, there may be specialized labor markets that are likely in disequilibrium. We develop a new methodology to improve the estimation of a reduced form disequilibrium model from the existing models by incorporating survey-based shortage indicators into the model and estimation. Our shortage-indicator informed disequilibrium model includes as a special case the foundational model of Maddala and Nelson (1974). We demonstrate the gains in information provided by our methodology. We show how the model can be implemented by applying it to the market for anesthesiologists, a profession susceptible to disequilibrium. In this application, we find that our new disequilibrium model informed by a shortage indicator fits the data better than the Maddala-Nelson model, and has better out-of-sample predictive power.
Keywords: J20; J44; I11; C18; 330; disequilibrium; labor demand; labor supply; shortage; maximum likelihood; health providers